A Multistimuli‐Responsive Photochromic Metal‐Organic Gel. (12th December 2013) - Wei, Shi‐Chao; Pan, Mei; Li, Kang; Wang, Sujuan; Zhang, Jianyong; Su, Cheng‐Yong
<x xml:space="preserve">Abstract</x> A photochromic metal‐organic gel with thermo‐, photo‐, and anion‐responsive behavior is obtained. Unusually, heating of the Al–ligand solution leads to gel formation and cooling to room temperature reverses the process to reform the solution. The gel is sensitive to weakly coordinating anions. Additionally, reversible photochromic transformations take place both in the solution and gel states, accompanied by reversibly switched luminescence. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>